The refining of titanium by crucibleless zone melting method - Kozhevnikov, O.E.; Pylypenko, M.M.; Shcherban, A.P.; Datsenko, О.А.; Pelykh, V.M.; Virych, V.D. (Вопросы атомной науки и техники, 2021)
The physical substantiation of titanium refining by crucibleless electron beam zone melting (ZM) method in vacuum was presented. Calculations of the equilibrium, limiting and effective distribution coefficients for impurity elements in the base metal were carried out. The refining of titanium was studied experimentally, and samples with a purity of 99.92 wt.% were received. The total content of impurities was reduced by a factor of 1.5 (from 0.12 to 0.08 wt.%). The concentration of interstitial impurities was significantly reduced (oxygen – by 1.3; carbon – by 2; nitrogen – by 2.5 times). The structure and microhardness were investigated.